How to design an interactive classroom with children to boost their epistemic curiosity - Özkara, Esra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
The aim of this study is to provide an interactive classroom environment for children to support their epistemic curiosity. In the study, curiosity-based questioning behaviors of children were examined based on the classroom conversations. The study was conducted in an early childhood classroom in Istanbul. The participants of the study are 10 children aged 5-6 years. For the study, the curiosity corner was set up in the classroom and children’s conversations were recorded during mealtimes (breakfast, lunch, and snack) for five months. For data analysis, qualitative conversation analysis method was used. Teacher-child conversations were transcribed verbatim. The conversations were coded based on linguistic type (statement and wh-, yes/no questions), causality (causal-not causal), topics (biology, convention, food/nutrition, motivation/ behavior, physical mechanism), teacher-child communicative interactions (initiation, elaboration/explanation, clarification). Findings show that, children asked mosly yes/no questions and they were more interested in biological phenomena, followed by nature, social convention, food motivation, and physical mechanisms. Only about 24% of children questions were “why” and “how” type of causal questions. The child communicative interaction in the classroom increased during the study. While children’s questions and initiations increased in April, later it was balanced. The teacher mostly elaborated on the children’s questions and asked clarification questions rather than engaging in initiations. The results demonstrate the importance of desining a preschool classroom to support inquiry-based learning.
Keywords: Epistemics.; Curiosity in children.